Benefits from heat pipe integration in H2/H2O fed SOFC systems. (1st May 2019) - Marocco, Paolo; Ferrero, Domenico; Lanzini, Andrea; Santarelli, Massimo
Graphical abstract: Highlights: Modelling of SOFC cells integrated with liquid metal heat pipes. Evaluation of maximum attainable current density using SOFC thermal limits. Maximum allowed current density higher with the presence of heat pipes. Possibility to operate at lower air flow rates with the presence of heat pipes. Economic profitability from heat pipe integration. Abstract: The Solid oxide fuel cell (SOFC) is an electrochemical energy-conversion device considered as a promising solution because of its high electrical efficiency, fuel flexibility and modularity with relevant environmental benefits. However, high temperatures and thermal gradients cause significant problems for the practical application of SOFC systems. SOFC operating conditions have to be maintained within specific bounds with limitation in the maximum achievable current density in order to avoid excessive degradation. Relevant air flow rate values are also required for a correct thermal management, dealing with the highly exothermicity of the SOFC operation. In this context, the integration of planar liquid metal heat pipes into the stack structure can contribute to reduce thermal gradients within the stack itself while lowering the parasitic consumption of the air blower since less convective cooling is required. In the present work, a model implementing different SOFC cells interposed between two planar heat pipe plates filled with sodium is developed. In particular, an SOFC system fed with a H2 /H2 O mixture is assessed (the most stringent thermal condition because of the absence of internal reforming). The maximum permissible current density is then evaluated by varying the air utilization factor (AU). The limiting operating conditions are identified by taking into account the following constraints: maximum cell temperature, maximum global and local temperature gradients and heat pipe transport limits. A comparison of the system with and without the presence of heat pipes is then carried out with the aim of highlighting the positive effects derived from their integration. Results from simulations show a remarkable improvement of the system performance with heat pipes, which allow to reach higher values of current densities (and so power densities) with a consequent economic benefit.